Project Based Learning in Pandemic Covid-19: The Implementation of ESD to Develop Students’ Critical Thinking Skills - Rahmayanti, Eneng; Hendayana, Sumar; Riandi, Riandi (Department of Integrated Science, Faculty of Mathematics and Natural Sciences, Universitas Negeri Semarang in Collaboration with Perkumpulan Pendidikan IPA Indonesia, 2021)
Distance learning is an alternative for implementing learning during the covid-19 pandemic. However, this system cannot be separated from problems, including the number of student complaints because of the tasks that must be done from each subject. This problem motivated us to carry out a qualitative research into the implementation of project-based learning that we have designed, using one integrated student worksheet for all subjects. This study aims to find a learning design that can minimize the burden and be able to contribute in developing students’ critical thinking by implementing education for sustainable development (ESD). The analysis was carried out using Transcript Based Lesson Analysis (TBLA). Based on the results of the analysis, it is proven that this learning is able to stimulate the active role of students in the learning process; building critical thinking skills of students in providing simple explanations by 17.39%, basic skills in observing and considering observations by 43.48%, stating hypotheses by 16.67% and deciding the action to be taken by 22.46%. From the results of the analysis of student conversation transcripts and questionnaires distributed to students, parents, and teachers, it can be concluded that this learning is able to reduce the accumulation of assignments, build students’ conceptual understanding, touch social, economic, and environmental aspects, build critical thinking skills and good character for students.